The Effect Of Profitability Ratios On Firm Value - Fitriani; Annisa Paramaswary Aslam; Anwar (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to analyze the influence of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) on firm value among technology companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research employs a quantitative approach using panel data regression analysis. The sample consists of nine technology companies selected through purposive sampling based on specific criteria. The results indicate that, individually, ROA, ROE, and NPM have no significant effect on firm value. Simultaneously, the three profitability variables also fail to exert a statistically significant combined influence on firm value. This suggests that profitability levels have not yet served as a positive signal to investors in assessing the value of technology firms in the capital market. Consequently, the findings contradict Signalling Theory, which posits that a company’s profitability provides investors with meaningful signals about its performance and future prospects. Instead, the results imply that during the research period, the value of technology firms in Indonesia was driven more by factors beyond profitability such as product innovation, adaptability to technological change, and the dynamic nature of the digital market..